Inovasi Produksi, Diversifikasi Inovasi Produk, dan Digital Marketing Kelompok UMKM Tempe di Desa Sepande Kecamatan Candi Kabupaten Sidoarjo - Fathulloh, Muhammad; Setiarno, Dandi Ari; Haq, Adam Rifqi Arinal; Kurniawan, Bagas; Ardiansyah, Muhammad Hilmidias; Permadani, Panji; Setyawan, Rizky Kurnia; Irwansyah, Mochammad Teguh; Latif, Nashorudin; Rahmadini, Annisa Lailatul; Fatwa, Ibrahim; Putra, Ringga Bagaskara; Setiawan, Mochammad Rendy Agus; Prakoso, Ardika Budi; Usada, Untung (Universitas Nahdlatul Ulama Sidoarjo, 2024)
Sepande Village is one of the villages located in Sidoarjo Regency Candi District which has more potential in the field of MSME making tempeh. The lack of variations of products and marketing that is still simple is an obstacle for MSMEs to improve the economy. Developing product variations and digital marketing management for MSME actors is needed. Therefore, through the program of increasing the capacity of Ormawa, the villagers of Sepande can utilize the potential of products and digital marketing to create businesses that benefit the residents of Sepande Village. The activities carried out with partners are developing production innovations by making production tools (mixing), developing products to create new product variants, and making digital marketing applications to increase the marketing potential of MSMEs in Sepande Village